Novel Co3O4 decorated with rGO nanocatalyst to boost microwave-assisted biodiesel production and as nano-additive to enhance the performance-emission characteristics of diesel engine - Maleki, Basir; Kalanakoppal Venkatesh, Yatish; Esmaeili, Hossein; Haddadi, Masoumeh; Mithun Prakash, Ravikumar; Balakrishna, Geetha R. (Energy (Oxford), 2024)
In this study, a novel Co3O4 decorated with rGO nanocatalyst was utilized in synergy with microwave heating as a novel approach for the generation of biodiesel. In this process, 98.04 % biodiesel yield was achieved by adopting response surface methodology algorithm under MEOH/oil molar ratio of 12.75:1, Co3O4@rGO loading of 1.53 wt%, microwave time of 7.17 min, and stirring speed of 512 rpm. The catalyst can be reused for seven times with biodiesel yields beyond 85 %. Co3O4@rGO was used as a nano-additive in the diesel engine to investigate the emission and performance of biodiesel blended with diesel. The Co3O4@rGO nanoparticles were dispersed into the B20 fuel with concentrations of 50 and 100 ppm. The outcomes discovered that the brake thermal efficiency of B20Co3O4@rGO50 is 1.22 % greater than B20, and the brake specific fuel consumption is declined by 5.05 %. The emissions from the diesel engine i.e. CO (29.88 %) and UHC (16.38 %) were significantly lowered compared to B20. The emission of NOx for B20Co3O4@rGO100 is 7.4 % lower than B20 and greater than conventional petrodiesel. Owing to its remarkable stability, excellent biodiesel yield, effective utilization in diesel engine, and high catalytic activity, the Co3O4@rGO is strongly proposed for industrial biodiesel generation utilizing microwave radiation. •A novel Co3O4@rGO employed for biodiesel generation by microwave-assisted.•High catalytic activity of Co3O4@ rGO in transesterification of Annona squamosa oil.•Maximum biodiesel yield of 98.04 % was achieved under optimal circumstances.•Co3O4@rGO nanocatalysts revealed promising recyclability up to the 7th cycle.•Disperse the Co3O4@rGO in B20 led to improved performance-emission diesel engine.